Conversion Disorder. Issue 3 (June 2018) - Feinstein, Anthony
ABSTRACT: PURPOSE OF REVIEW: This article provides a broad overview of conversion disorder, encompassing diagnostic criteria, epidemiology, etiologic theories, functional neuroimaging findings, outcome data, prognostic indicators, and treatment. RECENT FINDINGS: Two important changes have been made to the recent Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ( DSM-5 ) diagnostic criteria: the criteria that conversion symptoms must be shown to be involuntary and occurring as the consequence of a recent stressor have been dropped. Outcome studies show that the rate of misdiagnosis has declined precipitously since the 1970s and is now around 4%. Functional neuroimaging has revealed a fairly consistent pattern of hypoactivation in brain regions linked to the specific conversion symptom, accompanied by ancillary activations in limbic, paralimbic, and basal ganglia structures. Cognitive-behavioral therapy looks promising as the psychological treatment of choice, although more definitive data are still awaited, while preliminary evidence indicates that repetitive transcranial magnetic stimulation could prove beneficial as well. SUMMARY: Symptoms of conversion are common in neurologic and psychiatric settings, affecting up to 20% of patients. The full syndrome of conversion disorder, while less prevalent, is associated with a guarded prognosis and a troubled psychosocial outcome. Much remains uncertain with respect to etiology, although advances in neuroscience and technology are providing reproducible findings and new insights. Given the confidence with which the diagnosis can be made, treatment should not be delayed, as symptom longevity can influence outcome.